com

7. EXPONENTIAL SERIES AND LOGARITHMIC SERIES
PREVIOUS EAMCET BITS

1.

1 x 5x
( e + e ) = a 0 + a1x + a 2 x 2 + ..... ⇒ 2a1 + 23 a 3 + 25 a 5 + ....... =
e3x
3) 1
1) e
2) e −1
Ans:

[EAMCET 2009]
4) 0

Sol: e −2x + e 2x
⎡ ( 2x )2 ( 2x )4

= 2 ⎢1 +
+
+ .......⎥
2!
4!
⎢⎣
⎥⎦
⇒ a1 = 0, a 3 = 0, a 5 = 0..... and so on.

2.

1
1
1
+
+
+ ...... =
1.3 2.5 3.7
1) 2 log e2 − 2
2) 2 − 2 log e2

[EAMCET 2008]

3) 2 log e4

4) log e4

Ans: 2

1
1
1
1
+
+
+ ...... = ∑
Sol:
1.3 2.5 3.7
n =1 n ( 2n + 1)

1
1 ⎤
⎡1
= 2∑ ⎢ −
2n + 1 ⎥⎦
n =1 2n ( 2n + 1)
n =1 ⎣ 2n

= 2∑

⎡1 1 1 1

= 2 ⎢ − + − + .....⎥
2
3
4
5

⎡ 1 1 1

= 2 − 2 ⎢1 − + − + .....⎥ = 2 − 2 log e2
⎣ 2 3 4

3.

The coefficient of xk in the expansion of
1− k − k2
k!
Ans : 1

1)

Sol: Now

2)

k2 +1
k!

1 − 2x − x 2
is
e− x
3)

1− k
k!

[EAMCET 2007]

4)

1 − 2x − x 2
= (1 − 2x − x 2 ) e x
e− x

x 2 x3
xk
= ⎣⎡1 − 2x − x 2 ⎦⎤ ⎢1 + x + + + .... +
+ ....∞ ⎥
2! 3!
k!

x3
xk
x k +1
x2
xk
+
+ .....∞ ⎥
= ⎜1 + x + + .... +
+ ....∞ ⎟ −2 ⎢ x + + ..... +
2!
2!
k!
( k − 1)! k!

x4
xk
x k +1
− ⎢ x 2 + x 3 + + .... +
+
+ .....∞ ⎥
4!
( k − 2 )! ( k − 1)!

1

1
k!

Exponential series and logarithmic series
∴ coefficient of xk is

4.

1
2
1

k! ( k − 1) ! ( k − 2 ) !

1 2k k ( k − 1) 1 − k − k 2

=
k! k!
k!
k!
1
1
1
1

+ 3−
+ ... =
2
2 2.2 3.2 4.24
1
⎛3⎞
1)
2) log 3 ⎜ ⎟
4
⎝4⎠

[EAMCET 2007]
⎛3⎞
3) log e ⎜ ⎟
⎝2⎠

⎛2⎞
4) log e ⎜ ⎟
⎝3⎠

Ans: 2
Sol: x −

x 2 x3 x 4
+ − + ...... = log (1 + x )
2
3
4
2

3

4

⎛1⎞ ⎛1⎞ ⎛1⎞
1 ⎜⎝ 2 ⎟⎠ ⎜⎝ 2 ⎟⎠ ⎜⎝ 2 ⎟⎠
⎛ 1⎞
⎛3⎞

+

+ ..... = log ⎜1 + ⎟ = log 3 ⎜ ⎟
2
2
3
4
⎝ 2⎠
⎝2⎠
5.

1 − 2x
is
ex
n (1 + 2n )
2) ( −1)
n!

The coefficient of xn in

1 + 2n
n!
Ans :
1 − 2x
Sol:
= (1 − 2x ) e− x
ex

1)

(1 − 2x ) ⎢1 −

n!

6.

n

3) ( −1)

n

(1 − 2n )
n!

4) ( −1)

n

(1 + 4n )
n!

n

x x 2 x3
n x
+ + + ........ + ( −1)
+ .....⎥
1! 2! 3!
n!

Coefficient of xn in

( −1)
=

[EAMCET 2006]

2 ( −1)

n

( n − 1)!

1 − 2x
ex

⇒ (1)

If |x| < 1 and y = x −

n

(1 − 2n )
n!

x 2 x3 x 4
+ − + ...... then x is equal to
2
3
4

1) y +

y 2 y3
+ + ......
2 3

2) y −

y 2 y3 y 4
+ − + .....
2
3 4

3) y +

y 2 y3
+ + .....
2! 3!

4) y −

y 2 y3 y 4
+ − + .....
2! 3! 4!

Ans:
x 2 x3 x 4
Sol: y = x − + − + .....
2
3
4
y = log e (1 + x ) ⇒ 1 + x = e y

2

[EAMCET 2006]

Exponential series and logarithmic series
y2
+ .....
2!

⇒ 1+ x = 1+ y +
∴x = y +

y 2 y3
+ + .....
2! 3!

2n 2 + n + 1
=

n!
n =1

7.

[EAMCET 2005]

1) 2e − 1
Ans: 3

2) 2e + 1

3) 6e − 1

4) 6e + 1

2n 2 + n + 1 ∝ ⎡ 2n 2 n 1 ⎤
= ∑⎢
+ + ⎥
n!
n! n!⎦
n =1
n =1 ⎣ n!

Sol: Let s = ∑

∝ ⎡
2
3
1⎤
= ∑⎢
+
+ ⎥
( n − 1)! n!⎦
n =1 ⎣ ( n − 2 ) !

⎡ 1 1 1

⎡ 1 1
⎤ ⎡1 1 1

= 2 ⎢1 + + + + .... ∝ ⎥ + 3 ⎢1 + + + .... ∝ ⎥ + ⎢ + + + ... ∝ ⎥
⎣ 1! 2! 3!

⎣ 1! 2!
⎦ ⎣1! 2! 3!

= 2e + 3e + e − 1 = 6e – 1

8.

ak
If a < 1, b = ∑ , then a is equal to
n =1 k

1)

( −1)

k

bk

2)

k

n =1

k =1

( −1)

k −1

[EAMCET 2005]

( −1) b k

k =1 ( k − 1) !

bk

3)

k!

k

( −1) b k

k =1 ( k + 1) !

4)

k −1

Ans: 2

ak
a a 2 a3
= + + + .... ∝
1 2 3
k =1 k!

Sol: b = ∑

b = − log e (1 − a )
⎡ b b 2 b3

e − b = 1 − a ⇒ a = 1 − e − b = 1 − ⎢1 − + − + .... ∝ ⎥
⎣ 1! 2! 3!

∴a = ∑
k =1

( −1)

k −1

bk

k!

9.

The value of the series ∴ a = ∑
1) cosh ( x log ae )

k =1

( −1)

k −1

bk

[EAMCET 2004]

k!

2) coth ( x log ae )

3) sin h ( x log ae )

Ans: 3.

e x loge − e − x loge
Sol:
2
a

a

⎡ e x − e− x

x3 x5
x
=
+
+ + ....⎥

2
3! 5!

= sinh ⎡⎣ x log ae ⎤⎦

3

4) tan h ( x log ae )

Exponential series and logarithmic series
10.

Coefficient of x10 in the expansion of ( 2 + 3x ) e − x is
1) −

26
(10 )!

2) −

28
(10 )!

3) −

30
(10 )!

[EAMCET 2004]

4) −

32
(10 )!

Ans: 2
Sol:

( 2 + 3x ) e− x = ( 2 + 3x ) ⎢1 −

x x 2 x3
x 9 x10 ⎤
.....
+ − ...... +
1! 2! 3!
9! 10! ⎥⎦

∴ Coefficient of x in the above series
2 3
1
28
=
− =
( 2 − 30 ) ⇒ −
10! 9! 10!
10!
1 1+ 2 1+ 2 + 3
11.
+
+
+ .... is equal to
2! 3!
4!
e
e
1)
2)
2
3
Ans: 1

1 + 2 + 3 + ..... + n
Sol: = ∑
( n + 1)!
n =1
10

[EAMCET 2003]

3)

e
4

4)

e
5

n ( n + 1)
1 ∝
1
= ∑
2 n =1 ( n − 1) !
n =1 2 ( n + 1) n ( n − 1) !

=∑
=
12.

1⎡ 1 1 1
e
⎤ 1
1 + + + + .....⎥ = e =

2 ⎣ 1! 2! 3!
2
⎦ 2

If 0 < y < 21/ 3 and x ( y3 − 1) = 1 , then

⎛ y3 ⎞
1) log ⎜
3 ⎟
⎝ 2− y ⎠
Ans: 1
1
Sol: y3 − 1 =
x

⎛ y3 ⎞
2) log ⎜
3 ⎟
⎝1− y ⎠

2
2
2
+ 3 + 5 + ...... is equal to
x 3x 5x
⎛ 2y3 ⎞
3) log ⎜
3 ⎟
⎝ 1− y ⎠

[EAMCET 2003]

⎛ y3 ⎞
4) log ⎜
3 ⎟
⎝ 1 − 2y ⎠

x3 x5
1
⎛ 1+ x ⎞
x + + + ...... = log ⎜

3 5
2
⎝ 1− x ⎠
3
5

⎛1⎞ ⎛1⎞

1
1
x
x
⎛ 1 + 1/ x ⎞
= 2 ⎢ + ⎝ ⎠ + ⎝ ⎠ + .....⎥ ⇒ 2 × log ⎜

⎢x

3
5
2
⎝ 1 − 1/ x ⎠

⎡1 + y 3 − 1 ⎤
⎡ y3 ⎤
= log ⎢
=
log

⎢ 2 − y3 ⎥
3
⎣1 − y + 1 ⎦

13.

3
x2
x3
a 2
1 + x log + ( log e ) + ( log ae ) + ...... ( a > 0, x ∈ R ) is equal to
2!
3!
a
e

4

[EAMCET 2002]

Exponential series and logarithmic series

Sol: 1 +

x

2) ax

1) a
Ans: 2

3) a loge

4) x

x x2 x3
+ + + ........ = e x
1! 2! 3!

a
ax
x log ae ( x log e )
1+
+
+ ........ = e x loge = eloge = a x
1!
2!

a 2

14.

1+

1 + 2 1 + 2 + 22
+
+ ..... is equal to
2!
3!

1) e 2 + e
Ans: 4

Sol:

2

3) e 2 − 1

2) e 2

1 + 2 + 2 + ..... + 2
n!
n =1

n −1

[EAMCET 2002]

=∑
n =1

(2
1

n

4) e 2 − e

− 1)

2 −1
n!

2 −1
2
1
= ∑ −∑
n!
n =1
n =1 n!
n =1 n!

n

=∑

n

= ( e 2 − 1) − ( e − 1) = e2 − e
15.

2 2+4 2+4+6
+
+
+ ......
2!
3!
4!
1) e
2) e −1
Ans: 1

[EAMCET 2001]
3) e−2

4) e−3

2 (1 + 2 + 3 + .....n )
2 + 4 + 6 + ......... + 2n
⇒∑
( n + 1)!
( n + 1)!
n =1
n =1

Sol: = ∑

n ( n + 1)
1
⇒∑
n =1 ( n + 1) n ( n − 1) !
n =1 ( n − 1) !

=∑
= 1+
16.

1 1 1
+ + + ....... = e
1! 2! 3!

|x| < 1, the coefficient x3 in the expansion of log (1 + x + x 2 ) in ascending powers of x is
[EAMCET 2001]

2
3
Ans: 3

1)

2)

4
3

3) −

2
3

4) −

⎡ (1 + x + x 2 ) (1 − x ) ⎤
⎡1 − x 3 ⎤
⎥ = log ⎢
Sol: We have log (1 + x + x 2 ) = log ⎢

1− x
⎢⎣
⎥⎦
⎣ 1− x ⎦

⎤ ⎡

x6 x9
x2 x3
= log ⎡⎣1 − x 3 ⎤⎦ − log [1 − x ] = − ⎢ x 3 + + + ......⎥ + ⎢ x + + + ......⎥
2
3
2
3

⎦ ⎣

5

4
3